A Practical-Theological Phenomenology of Joy Learning from L’arche - Ommen, Armand Léon van; Land, Julie Marie (2020)
In recent years, joy has received renewed attention as a central theological concept. However, voices from lived experience are largely lacking in this discussion. This article studies the question of what joy looks like and what its essence is in one particular exemplar of joy, i.e., the L’Arche communities. Based on fieldwork, which included participant observation and interviews in four L’Arche communities, as well as an interview with the founder of L’Arche, Jean Vanier, this article proposes a practical-theological phenomenology of joy.
Keywords: Henri Nouwen; Jean Vanier; L’Arche; Community; Disability; Joy